The Importance of IgG Avidity and the Polymerase Chain Reaction in Treating Toxoplasmosis during Pregnancy: Current Knowledge - João Bortoletti Filho; Edward Araujo Júnior; Natália da Silva Carvalho; Talita Micheletti Helfer; Priscila de Oliveira Nogueira Serni; Luciano Marcondes Machado Nardozza; Antonio Fernandes Moron (Interdisciplinary Perspectives on Infectious Diseases)
A brief report on the nature and epidemiology of T. gondii infection is firstly presented. The importance of the specific IgG avidity test and polymerase chain reaction (PCR) for toxoplasmosis is discussed, along with their significance and importance as auxiliary methods for determining the most likely time for the initial infection by this coccidian and for defining the therapeutic strategy. Lastly, practical comments are made in relation to the classical therapeutic regimens, with special attention to the indications for fetal treatment, when this is necessary.